2015
DOI: 10.1007/s11060-015-1858-2
|View full text |Cite
|
Sign up to set email alerts
|

Genomic predictors of patterns of progression in glioblastoma and possible influences on radiation field design

Abstract: We present a retrospective investigation of the role of genomics in the prediction of central versus marginal disease progression patterns for glioblastoma (GBM). Between August 2000 and May 2010, 41 patients with GBM and gene expression and methylation data available were treated with radiotherapy with or without concurrent temozolomide. Location of disease progression was categorized as within the high dose (60 Gy) or low dose (46 Gy) volume. Samples were grouped into previously described TCGA genomic groupi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In the era of concurrent chemoradiotherapy with TMZ, many studies have reported that local recurrence is still a major failure pattern in limited-margin radiotherapy. Recently, several studies reported improved local control but higher rates of distant failures in patients with favorable prognostic factors including O 6 -methylguanine-DNA methyltransferase (MGMT) promoter methylation or extensive surgical resection 14 15 16 17 18 . However, there is no report so far concerning the relationship between radiotherapy volume and these prognostic factors.…”
mentioning
confidence: 99%
“…In the era of concurrent chemoradiotherapy with TMZ, many studies have reported that local recurrence is still a major failure pattern in limited-margin radiotherapy. Recently, several studies reported improved local control but higher rates of distant failures in patients with favorable prognostic factors including O 6 -methylguanine-DNA methyltransferase (MGMT) promoter methylation or extensive surgical resection 14 15 16 17 18 . However, there is no report so far concerning the relationship between radiotherapy volume and these prognostic factors.…”
mentioning
confidence: 99%
“…The location of the tumor is also to be taken into account. Studies conducted on patients whose tumors come into contact with the SVZ have indicated decreased OS and PFS 15,32. This could be explained by the fact that the NSC located in the SVZ can increase the aggressiveness of the tumor 24,31.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the interaction between GBM and the SVZ has been highlighted, as the tumors coming into contact with the area that contains NSC have a worse prognosis than those located at a distance 2,3,11,17,25,36. The subject needs more research because there are also studies that could not confirm the prognostic role of SVZ invasion by GBM 15,16…”
Section: Introductionmentioning
confidence: 99%
“…At WFBMC, genomic techniques for data processing and evaluation were previously described by Holmes et al [14]. In brief, Affymetrix Human Exon 1.0 ST GeneChips (Affymetrix, Santa Clara, CA) and Infinium HumanMethylation (HM) 450 BeadChip from Illumina (Illumina, San Diego, CA) were used for genomic analysis offresh frozen tissue from the Brain Tumor Center of Excellence Tumor Bank at WFBMC [15]. Of note, tissue banking was performed predominantly on patients with tumor resection as opposed to stereotactic biopsy as the latter tended to yield an insufficient quantity of tissue.…”
Section: Genomic Analysismentioning
confidence: 99%